Non-linear longitudinal associations between moderate-to-vigorous physical activity and adiposity across the adiposity distribution during childhood and adolescence: Gateshead Millennium Study - Janssen, Xanne (Int J Obes (Lond), 2018)
OBJECTIVE: Insufficient moderate-to-vigorous intensity physical activity (MVPA) is harmful for youth; however, the evidence for differential effects by weight status is limited. The study aimed to examine associations between MVPA and adiposity by weight status across childhood and adolescence. METHODS: Participants were from the Gateshead Millennium Study. Physical activity and body composition measures were taken at age 7 y (n = 502; measures taken between October 2006 and December 2007), 9 y (n = 506; October 2008–September 2009), 12 y (n = 420; October 2011–September 2012), and 15 y (n = 306; September 2014–September 2015). Participants wore an ActiGraph GT1M and epochs were classified as MVPA when accelerometer counts were ≥574 counts/15 s. Weight and height were measured using standardized methods and fat mass using bioelectrical impedance. Associations between MVPA and changes in BMI and FMI were examined by weight status using quantile regression. RESULTS: Higher MVPA was associated with lower FMI for the 25th, 50th, 75th, and 90th percentile and lower BMI at the 50th, 75th, and 90th percentile, independent of accelerometer wear time, sex, and sedentary time. The association between MVPA and change in adiposity was stronger in the higher than lower FMI and BMI percentiles (e.g., 1 h/day more MVPA was associated with a 1.5 kg/m(2) and 2.7 kg/m(2) lower FMI at the 50th and 90th FMI percentiles, respectively). CONCLUSIONS: The effect of MVPA on adiposity in the higher adiposity percentiles is stronger than reported to date. Given overweight and obese children are the highest risk group for later obesity, targeting MVPA might be a particularly effective obesity prevention strategy.